A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini) - Qi, Mu-Jie; Han, Hui-Lin (Zootaxa, 2017)
The genus Alienia Fibiger, 2011 of the tribe Micronoctuini of Hypenodinae is revised. Two new species: Alienia fibigeri sp.n. and Alienia cambodiaa sp.n. are described from Cambodia; a new species, Alienia laosa sp.n. from Laos described. A key for identification of Alienia based on male genitalia is present. The adult and genitalia of the new species are illustrated.